A genome-wide screen identifies genes required for erythroid differentiation - Greggory Myers; Ann Friedman; Lei Yu; Narges Pourmandi; Claire Kerpet; Masaki A. Ito; Rilie Saba; Vi Tang; Ayse Bilge Ozel; Ingrid L. Bergin; Craig N. Johnson; Chia-Jui Ku; et al. (Nature Communications)
Abstract The complete array of genes required for terminal erythroid differentiation remains unknown. To address this knowledge gap, we perform a genome-scale CRISPR knock-out screen in the human erythroid progenitor cell line HUDEP-2 and validate candidate regulators of erythroid differentiation in a custom secondary screen. Comparison of sgRNA abundance in the CRISPR library, proerythroblasts, and orthochromatic erythroblasts, resulted in the identification of genes that are essential for proerythroblast survival and genes that are required for terminal erythroid differentiation. Among the top genes identified are known regulators of erythropoiesis, underscoring the validity of this screen. Notably, using a Log2 fold change of <−1 and false discovery rate of <0.01, the screen identified 277 genes that are required for terminal erythroid differentiation, including multiple genes not previously nominated through GWAS. NHLRC2, which was previously implicated in hemolytic anemia, was a highly ranked gene. We suggest that anemia due to NHLRC2 mutation results at least in part from a defect in erythroid differentiation. Another highly ranked gene in the screen is VAC14, which we validated for its requirement in erythropoiesis in vitro and in vivo. Thus, data from this CRISPR screen may help classify the underlying mechanisms that contribute to erythroid disorders.